2017
DOI: 10.5121/ijcsit.2017.9107
|View full text |Cite
|
Sign up to set email alerts
|

Research on Decision Making Regarding in Dating Events for Unmarried Female Junior High School Teachers

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The tendency to cooperate, help, and care for the other seems to be one of the main criteria for selecting a long-term relationship partner for men and women (Buss and Schmitt 2019;Shackelford and Buss 2000). Several studies, have consistently shown the preference for partners with high levels of agreeableness or who show care for the partner (e.g., Boxer et al 2015;Huang et al 2017;Shackelford and Buss 2000;Souza et al 2016b; for a review, see Nettle and Clegg 2008). People with high levels of agreeableness tend to be true, loyal, and cooperative with their romantic partners, willing to invest in their relationship, and to maintain harmonious relationships with others (Nettle and Clegg 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The tendency to cooperate, help, and care for the other seems to be one of the main criteria for selecting a long-term relationship partner for men and women (Buss and Schmitt 2019;Shackelford and Buss 2000). Several studies, have consistently shown the preference for partners with high levels of agreeableness or who show care for the partner (e.g., Boxer et al 2015;Huang et al 2017;Shackelford and Buss 2000;Souza et al 2016b; for a review, see Nettle and Clegg 2008). People with high levels of agreeableness tend to be true, loyal, and cooperative with their romantic partners, willing to invest in their relationship, and to maintain harmonious relationships with others (Nettle and Clegg 2008).…”
Section: Discussionmentioning
confidence: 99%